Mouth rinsing and ingesting unpleasant salty or bitter solutions after heavy-intensity cycling does not influence sprint performance or knee-extensor force in trained cyclists - Gray, E. A.; Cavaleri, R.; Siegler, J. C. (International Journal of Sports Physiology and Performance, 2024)
Purpose: The present study investigated the effect of unpleasant salty or bitter tastes on cycling sprint performance and knee-extensor force characteristics in different fatigue states.